Influence of early exercise on bone mineral density in equine distal third metacarpal condyles - Zimmerman, Chelsea A., author; Duesterdieck, K., author; Kawcak, Chris E., author (Colorado State University. Libraries, 2005)
Although musculoskeletal injuries have a large impact on the horse industries, little is known as to the effects of early exercise. Prior research suggests that repeated loading and exercise leads to an increase in higher density, low quality bone that is slow to repair. However, adapting the musculoskeletal system to high intensity exercise early may lead to less injuries in the equine metacarpophalangeal joint (MCP), a common site of fracture in Thoroughbred (TB) racehorses. The objective of this study was to determine bone density patterns in the equine MCP joints of young TBs to evaluate the effects of early exercise.
Keywords: Thoroughbred horse -- Exercise -- Physiological aspects; Bone densitometry